Effects of liquid smoke preparations on shelf life and growth of wild type mold and Aspergillus flavus in a model semi moist pet food - Deliephan, Aiswariya; Dhakal, Janak; Subramanyam, Bhadriraju; Aldrich, Charles G. (Frontiers in Microbiology, 2023)
Liquid smoke is a naturally derived flavor component and preservative with known antimicrobial properties. To our knowledge, there is a paucity of information on antifungal potential of liquid smoke against toxigenic fungi like Aspergillus flavus that produce mycotoxins in human and pet foods. Semi-moist pet food with high moisture content (20–30%) is susceptible to mold contamination and requires intervention. The objectives of this study were to determine the effects of liquid smoke preparations on the growth of wild-type mold and A. flavus in semi-moist pet food. Semi-moist pet food was formulated with eight different liquid smoke preparations (S1–S8) containing varying amounts of organic acids, phenol and carbonyl compounds (ranging from low to high) at 0% (untreated), 0.5, 1, 2, and 4% (w/w). A positive control consisted of 0.2% potassium sorbate known to inhibit mold growth. Shelf life was estimated by storing the samples at 28°C and 65–70% RH over 30 days and recording the number of days until the appearance of visible wild-type mold. In another experiment, samples were spot inoculated with A. flavus (∼10,000 CFU/mL), incubated at 25°C, and analyzed for fungal growth at sampling intervals of 2 days over a 35-day period. Liquid smoke at 0.5, 1, 2, and 4% extended the shelf life of samples on an average by a total of 11.6, 12.5, 17.2, and 24.1 days when compared to the untreated samples (7.7 days). The smoke preparations Cloud S-C100 (S3) and Code-10 (S6) (high carbonyl, medium/low phenol) were the most effective (P < 0.05) in prolonging the number of days to visible mold growth (26–28 days). In the challenge study with A. flavus, Cloud S-C100 (S3), Cloud S-AC15 (S8) (high to medium carbonyl, low phenol), and Code 10 (S6) (base smoke) reduced (P < 0.05) mold counts by 1.0, 1.7, and 2.5 logs when compared to the untreated samples at 1, 2, and 4%, respectively. Addition of smoke at 0.5% did not reduce mold counts. The carbonyl preparations of liquid smoke were the most effective at enhancing shelf life of semi-moist pet food, and at inhibiting A. flavus growth.